(untitled) (Journal of Comparative & International Higher Education, 2022)
China remains the top country of citizenship for international students and female students (married and single) comprise part of Chinese international students. However, female international students as a marginalized group face multiple challenges and parental, marital, personal, and cross-cultural situational barriers. Relying on an auto-ethnographic inquiry, this study digs into my experiences and stories as a Chinese female graduate student in Canada to examine and connect with the academic climate and broader communities. Specifically, the gender-based, culture-based, and race-based challenges that I faced during my studies at a Canadian university including my coping strategies are explored. The constructivist paradigm as a theoretical framework is used to delve into my perceptions and understanding of my lived experiences. Data was collected from my journals, memories, and emails written during my study in Canada. Based on my experience, this study unveils motivation, knowledge, and organizational gaps faced by the female group because of gender inequality, and cross-cultural and cross-racial differences.